Design of a parallel coupled microstrip line bandpass filter on the RO4003C substrate - Hock G.C.; Chakrabarty C.K. (2023)
This paper describes the improvement of the artwork for a microwave circuit in order to have the dimensions of the desired physical realization. In highlighting the general modification, a fifth order parallel edge-coupled bandpass filter is designed and analyzed. The filter design, in most cases, is complicated by the presence of the physical constraint as the resulting artwork is not easily fabricated. Hence, the filter is designed to have matching stubs in order to ease the circuit fabrication. In designing the circuit, electronics design automation tool with filter synthesis wizard and optimizing features is used. The circuit is implemented on microstrip line technology and RO4003C substrate is used. 2006 IEEE.